1.
[tex]\displaystyle \text{if }\quad G=x- \frac{C}{x} \\\\[/tex]
[tex]x \neq 0 [/tex]
Multiply both sides by x:
[tex]\displaystyle Gx=x\bigg(x- \frac{C}{x}\bigg )\\\\Gx=x^2-C[/tex]
Subtract from both sides Gx:
[tex]Gx-Gx=x^2-C-Gx\\x^2-Gx-C=0[/tex]
Then solve this equation:
[tex]\displaystyle x^2-Gx-C=0\\\\x_{1,2}= \frac{G\pm \sqrt{G^2+4C} }{2} [/tex]
2.
[tex]\displaystyle\text{if}\quad G= \frac{x-C}{x} [/tex]
[tex]x \neq 0[/tex]
Multiply both sides by x:
[tex]Gx=x-C[/tex]
Subtract from both sides Gx:
[tex]x-C-Gx=0[/tex]
Then solve this equation:
[tex]\displaystyle x-Gx-C=0\\x(1-G)=C\\x= \frac{C}{1-G} [/tex]